Incarnational Psychotherapy: Christ as the Ground of Being for Integrating Psychology and Theology - Rennebohm, Samuel B. (Pastoral psychology, 2021)
The integration of psychology and theology is often sought as a layering of intellectual abstractions from biblical and psychological sources. Though scriptural and scientific data may partially define the reality of God and human psychology, the Truth is an embodied act, God made incarnate among us as Christ. The common ground for integration of psychology and theology must then be this ground of being, the incarnate presence of Jesus Christ among us. The basis for integration is derived theologically from the relational nature of and God and the ongoing revelation of Christ to humankind through incarnational presence (i.e., social theology) and psychologically from the preeminence of relationships in shaping human development, well-being, and psychological distress (i.e., interpersonal psychology). This paper reviews both traditions in turn before then discussing the incarnation of Christ as the ground of being for their integration. Incarnational relational enactment is proposed to characterize the transformative presence of Christ in the healing work of a therapeutic relationship. This process is described as immediate, personal, unconditional, and dialectical, ultimately leading to a literal renewing of the mind.